HUBUNGAN AKTIVITAS FISIK DAN GAYA HIDUP DENGAN KEJADIAN DIABETES MELITUS DI WILAYAH KERJA X KOTA BENGKULU - Nurlindawatai, Nurlindawatai; Puspita, Tari (ANJANI Journal (Medical Science & Healthcare Studies), 2024)
Intoduction: Type 2 diabetes mellitus is the most common type of diabetes found. Approximately 9.7 million women in America have diabetes. Indonesia is ranked 6th in the incidence of diabetes mellitus in the world. Type 2 diabetes mellitus is often also called lifestyle diabetes because the causes are apart from hereditary factors, environmental factors including physical activity, and lifestyle are also causes of diabetes mellitus. To analyze the factors causing type 2 diabetes mellitus in women of reproductive age. The research was conducted using qualitative methods, which produced descriptive data in the form of written interviews with informants. The informants in this study were 10 women aged 30 – 65 years who lived in the work area of Puskesmas X. Conclusion: The results of this study are that there is a relationship between physical activity and lifestyle and the incidence of diabetes mellitus.